An efficient concrete plastic damage model for crack propagation in gravity dams during seismic action - Nghia-Nguyen, Trong; Thanh Cuong, Le; Khatir, Samir; Hoang, Le Minh; Chaiyaput, Salisa; Abdel Wahab, Magd (My University, 2024)
Purpose: Concrete gravity dams are important structures for flood control and hydraulic power generation, but they can be vulnerable to seismic activity due to ground movements that trigger crack propagation. Design/methodology/approach: To better understand the factors that affect the stability of concrete gravity dams against concrete fracture during earthquakes, a concrete plastic damage model has been utilized with two new expressions to simulate compressive and tensile damage variables. Findings: The findings showed that the crack patterns were strongly influenced by the concrete’s strength. The simulation results led to the proposal of appropriate concrete properties aimed at minimizing damage. These findings, together with the proposed model, offer significant insights that can enhance the safety and stability of concrete gravity dam structures. Originality/value: This study offers a comprehensive analysis of concrete behavior under varying grades and introduces simple and robust expressions for evaluating concrete parameters in plastic damage models. The versatility of these expressions enables accurate simulation of stress-strain curves for different grades, resulting in excellent agreement between model results and experimental findings. The simulation of the Koyna Dam case study demonstrates a similarity in crack patterns with previous simulations and field observations.
Keywords: Concrete gravity dam; Plastic damage model; Seismic analysis